Impact of the COVID-19 pandemic on tuberculosis management in Spain. (July 2021) - Aznar, M.L.; Espinosa-Pereiro, J.; Saborit, N.; Jové, N.; Sánchez Martinez, F.; Pérez-Recio, S.; Vitoria, A.; Sanjoaquin, I.; Gallardo, E.; Llenas-García, J.; Pomar, V.; García, I.O.; et al.
Highlights: Most tuberculosis (TB) units reported changes in their TB team operations. TB patients diagnosed during COVID-19 showed more extended pulmonary forms. Latent TB infections in children household contacts were higher in 2020. Active TB in children household contacts were higher in 2020. Abstract: Background: The impact of COVID-19 on the diagnosis and management of tuberculosis (TB) patients is unknown. Methods: Participating centres completed a structured web-based survey regarding changes to TB patient management during the COVID-19 pandemic. The study also included data from participating centres on patients aged ≥18 diagnosed with TB in 2 periods: March 15 to June 30, 2020 and March 15 to June 30, 2019. Clinical variables and information about patient household contacts were retrospectively collected. Results: A total of 7 (70%) TB units reported changes in their usual TB team operations. Across both periods of study, 169 patients were diagnosed with active TB (90 in 2019, 79 in 2020). Patients diagnosed in 2020 showed more frequent bilateral lesions in chest X-ray than patients diagnosed in 2019 ( P  = 0.004). There was a higher percentage of latent TB infection and active TB among children in households of patients diagnosed in 2020, compared with 2019 ( P  = 0.001). Conclusions: The COVID-19 pandemic has caused substantial changes in TB care. TB patients diagnosed during the COVID-19 pandemic showed more extended pulmonary forms. The increase in latent TB infection and active TB in children of patient households could reflect increased household transmission due to anti-COVID-19 measures.